Produtos de desacumulação : o uso de life-care annuities em Portugal - Martins, Catarina Alexandra Ferreira (2019)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management